Romantik in der Kunst der Gegenwart : Sammlung Murken. - Becker, Wolfgang; Bunk, Holger; Bömmels, Peter; Girke, Raimund; Klütsch, Margot; Kohl, Thomas; Loch, Anne; Maslin, Steven; Muggenthaler, Johannes; Murken, Axel & Christa; Murken, Axel Hinrich; Murken, Christa; et al. (Köln : Wienand Verlag, 1993)
Bach, Michael ; Beuys, Joseph ; Bijl, Guillaume ; Blanchard, Rèmy ; Bömmels, Peter ; Bunk, Holger ; Dahn, Walter ; Feldmann, Hans-Peter ; Gasiorowski, Gérard ; Gerdes, Ludger ; Germana, Mimmo ; Girke, Raimund ; Finlay, Ian Hamilton ; Hötzel, Bernd ; Ikemura, Leiko ; Jaeger, Wilhelm ; Jünger, Bernd ; Klinkan, Alfred ; Knap, Jan ; Kohl, Thomas ; Koons, Jeff ; Kostabi, Mark ; Lanneau, Patrick ; Lassnig, Maria ; Leisgen, Barbara ; Leisgen, Michaël ; Loch, Anne ; Marioni, Joseph ; Maslin, Steven ; Miller, John ; Morgan, Tony ; Muggenthaler, Johannes ; van Ofen, Michael ; Parrino, Steven ; Raeck, Karina ; Richter, Gerhard ; S., Laura ; Schulze, Andreas ; Stepanek, Alice ; Strode, Thaddeus ; Tannert, Volker ; van de Ven, Lidwien; Wanner, Franz
biografie
Duits
Romantik in der Kunst der Gegenwart : Sammlung Murken., Ludwig Forum für Internationale Kunst Aachen, 4.6. bis 22.8.1993, Kulturzentrum Bayer AG, Leverkusen, 28.11.1993 bis 23.1.1994, Kunsthalle Dominikanerkirche, Osnabrück, 20.2. bis 27.3.1994, Kunstamt Kreuzberg, Berlin, 1994, Kunstmuseum Thun, Thun/Schweiz, 1994, Städtische Galerie Jesuitenkirche, Aschaffenburg, 1994, Landesmuseum, Mainz, 1994/1995, Zeppelin-Museum Technik & Kunst, Friedrichshafen, 1995
boek